Biomarkers and the Development of a Personalized Medicine Approach in Spinal Muscular Atrophy - Kariyawasam, Didu S. T.; D'Silva, Arlene; Lin, Cindy; Ryan, Monique M.; Farrar, Michelle A. (Frontiers in Neurology, 2019)
Recent unprecedented advances in treatment for spinal muscular atrophy enabled patients to access the first approved disease modifying therapy for the condition. There are however many uncertainties, regarding timing of treatment initiation, response to intervention, treatment effects and long-term outcomes, which are complicated by the evolving phenotypes seen in the post-treatment era for patients with spinal muscular atrophy. Biomarkers of disease, with diagnostic, prognostic, predictive and pharmacodynamic value are thus urgently required, to facilitate a wider understanding in this dynamic landscape. A spectrum of these candidate biomarkers, will be evaluated in this review, including genetic, epigenetic, proteomic electrophysiological, and imaging measures. Of these, SMN2 appears to be the most significant modifier of phenotype to date, and its use in prognostication shows considerable clinical utility. Longitudinal studies in patients with SMA highlight an emerging role of circulatory markers such as neurofilament, in tracking disease progression and response to treatment. Furthermore, neurophysiological biomarkers such as CMAP and MUNE values show considerable promise in the real word setting, in following the dynamic response and output of the motor unit to therapeutic intervention The specific value for these possible biomarkers across diagnosis, prognosis, prediction of treatment response, efficacy and safety will be central to guide future patient-targeted treatments, the design of clinical trials and understanding of the pathophysiological mechanisms of disease and intervention.